Feeding habits and trophic niche overlap of the aquatic Orthoptera associated to macrophytes - Capello, Soledad (2012)
The dietary analysis is a frequent first step in studying an animal?s ecology because diet directly reflects resource use and can provide insight into habitat utilization and competitive interactions. Little is known concerning the Orthoptera species that inhabit moist or wet environments because usually such species do not become pests. We hypothesized that the aquatic orthopterans are feeding only on few macrophytes and they show trophic niche overlap. The feeding habits of seven species of Orthoptera associated to macrophytes, the botanical composition of diet of these insects and their trophic niche breadth and overlapping were analyzed. The diet composition by microanalysis of feces under an optical microscope and frequency of occurrence of each plant, food niche breadth, niche overlap and the food specialization level of every species were determined. Only Paulinia acuminata, Marellia remipes and Cornops aquaticum consumed aquatic plants exclusively. The water hyacinth (Eichhornia crassipes) was the unique macrophyte consumed by all the species of Orthoptera, although in different proportions. The highest trophic niche breadth was shown by Coryacris angustipennis and the highest Berger-Parker index value was reached by C. aquaticum, showing a high specificity. The species C. aquaticum, C. angustipennis, Conocephalus sp. and Scudderia sp. show a niche overlapping; however they may live in the same habitats because the resources are very abundant. The diet composition of these species (except C. aquaticum) is the first time that was analyzed and it is important information to explain the Orthoptera assemblages associated to macrophytes of the Middle Paraná River.